Vibration and jitter of free-flowing thin liquid sheets as target for high-repetition-rate laser-ion acceleration - Cao, Zhengxuan; Peng, Ziyang; Shou, Yinren; Zhao, Jiarui; Chen, Shiyou; Gao, Ying; Liu, Jianbo; Wang, Pengjie; Mei, Zhusong; Pan, Zhuo; Kong, Defeng; Qi, Guijun; et al. (Frontiers in Physics, 2023)
Very thin free-flowing liquid sheets are promising targets for high-repetition-rate laser-ion acceleration. In this work, we report the generation of micrometer-thin free-flowing liquid sheets from the collision of two liquid jets, and study the vibration and jitter in their surface normal direction. The dependence of their motion amplitudes on the generation parameters is studied in detail. The origins of the vibration and jitter are discussed. Our results indicate that when the generation parameters are optimized, the motion amplitudes in the stable region can be stabilized below 3.7 μm to meet the stringent requirement of sheet position stability for a tight-focusing setup in laser-ion acceleration experiments.